Longitudinal associations between beta-endorphin, nonsuicidal self-injury and comorbid psychopathology - Kao, Han-Tin; Mürner-Lavanchy, Ines M.; Lerch, Stefan; Stosch, Elisabeth von; Berger, Thomas; Koenig, Julian; Kaess, Michael (Psychiatry research, 2024)
Homeostasis models posit that nonsuicidal self-injury (NSSI) serves, in part, to upregulate the endogenous opioid system in order to compensate for an opioid deficiency. A few studies have demonstrated lower basal levels of beta-endorphin (BE), an endogenous opioid, in individuals with NSSI. However, longitudinal studies are missing. Hence, the present study aimed to investigate the longitudinal associations between NSSI, comorbid psychopathology (i.e., borderline personality disorder and depressive symptoms), pain sensitivity and basal BE levels in adolescents with NSSI. N = 53 adolescents with NSSI disorder undergoing specialized treatment participated in baseline and one-year follow-up assessments. BE was measured in plasma; pain sensitivity was assessed with a heat pain stimulation paradigm. Associations between BE and change in NSSI, borderline personality disorder and depressive symptoms as well as pain sensitivity were examined using negative binomial and linear regression analyses. We found that an increase in basal BE was significantly associated with a decrease in depressive symptoms. No associations between BE and NSSI, borderline personality disorder symptoms or pain sensitivity were observed. Our findings may confirm a role of plasma BE in the etiology of depressive symptoms but challenge current models of endogenous opioid homeostasis in NSSI.